The development of home made appratus for the production of biodiesel from new cooking oil - Muhammad Faizal, Zainal Abidin (2006)
Due to the increase in the price of the petroleum and the environmental concerns about pollution coming from car gases, biodiesel is becoming a developing area of high concern. Biodiesel is the name of a clean burning alternative fuel, produced from domestic, renewable resources. Biodiesel contains no petroleum, but it can be blended at any level with petroleum diesel to create a biodiesel blend. It can be used in compression ignition (diesel) engines with little or no modifications. Biodiesel is simple to use, biodegradable, nontoxic, and essentially free of sulfur and aromatics. Developing of biodiesel is not so hard process. There are different ways of production, with different kinds of raw materials, such as crude oil, new cooking oil or frying cooking oils. In this project, the new cooking oil will be used to produce biodiesel. Biodiesel is made through a chemical process called transesterification whereby the glycerin is separated from the fat or vegetable oil. The process leaves behind two products, that is methyl esters (biodiesel) and glycerin, a valuable by product usually sold to be used in soaps and other products. Before biodiesel can be produce, there is some circumstance to face. One of the problems is the apparatus. During this time, there are no small scale biodiesel have been developed. The main objective of this project is to develop a home made apparatus for biodiesel production. After the apparatus have been made, five test batch will be held with each batch is different from it’s Methanol quantity, to determine the best ratio of Methanol to oil used to get high yield of biodiesel. The last step in this thesis is analyzing the result using Gas Chromatography. The first observation showed that the best ratio Methanol to oil is 4:1. But, GC result showed that all five samples contain high of methyl palmitate that is major component of biodiesel. So, it can conclude that the product that comes from this apparatus is biodiesel.